What Is a Language? Who Is Bilingual? Perceptions Underlying Self-Assessment in Studies of Bilingualism - Wagner, Danika; Bialystok, Ellen; Grundy, John G. (Frontiers in Psychology, 2022)
Research on the cognitive consequences of bilingualism typically proceeds by labelling participants as “monolingual” or “bilingual” and comparing performance across these groups on some measure. It is well known that this approach has led to inconsistent results. However, the approach assumes that there are clear criteria to designate individuals as monolingual or bilingual, and more fundamentally, to determine whether a communication system counts as a unique language. Both these assumptions may not be correct. The problem is particularly acute when participants are asked to make this classification themselves or simply report how many languages they speak. Participants’ responses to these questions are shaped by their personal perceptions of the criteria for making these judgments. The present study investigated the perceptions underlying judgments of bilingualism by asking 528 participants to judge the extent to which a description of a fictional linguistic system constitutes a unique language, and the extent to which a description of a fictional individual’s linguistic competence qualifies that person as bilingual. The results show a range of responses for both concepts, indicating substantial ambiguity for these terms. Moreover, participants were asked to self-classify as monolingual or bilingual and these decisions were not related to more objective information regarding degree of bilingual experience obtained from a detailed questionnaire. These results are consistent with the notion that bilingualism is not categorical and that specific language experiences are important in determining the criteria for being bilingual. The results impact interpretations of research investigating group differences on the cognitive effects of bilingualism.